2022
DOI: 10.3389/fimmu.2021.662218
|View full text |Cite
|
Sign up to set email alerts
|

Precision Vaccine Development: Cues From Natural Immunity

Abstract: Traditional vaccine development against infectious diseases has been guided by the overarching aim to generate efficacious vaccines normally indicated by an antibody and/or cellular response that correlates with protection. However, this approach has been shown to be only a partially effective measure, since vaccine- and pathogen-specific immunity may not perfectly overlap. Thus, some vaccine development strategies, normally focused on targeted generation of both antigen specific antibody and T cell responses,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 268 publications
(364 reference statements)
0
32
0
Order By: Relevance
“…Previously, we have demonstrated that cGAMP is a promising adjuvant candidate for early life immunization 13 . We have also demonstrated that optimization of vaccine formulation and delivery route can enhance the adjuvanticity potential of TLR7/8 agonists (e.g., CL075) 1,3 , specifically by encapsulation within PEG-b-PPS nanocarriers 12 . Our team has validated PEG-b-PPS PSs for nontoxic adjuvant delivery to mice with enhanced targeted uptake by DCs and monocytes [10][11][12] .…”
Section: Admixture Of Cgamp-ps and Cl075-ps Enhances Th1-polarized Ag...mentioning
confidence: 91%
See 2 more Smart Citations
“…Previously, we have demonstrated that cGAMP is a promising adjuvant candidate for early life immunization 13 . We have also demonstrated that optimization of vaccine formulation and delivery route can enhance the adjuvanticity potential of TLR7/8 agonists (e.g., CL075) 1,3 , specifically by encapsulation within PEG-b-PPS nanocarriers 12 . Our team has validated PEG-b-PPS PSs for nontoxic adjuvant delivery to mice with enhanced targeted uptake by DCs and monocytes [10][11][12] .…”
Section: Admixture Of Cgamp-ps and Cl075-ps Enhances Th1-polarized Ag...mentioning
confidence: 91%
“…Collimated X-rays with 10 keV (wavelength λ = 1.24 Å) was utilized to measure samples. Sample measurement was performed in the q-range 0.001 to 0.5 Å - 1 , which was calibrated using silver behenate. The final scattering data of samples was obtained using PRIMUS 2.8.2 software after subtracting solvent buffer scattering from sample scattering.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zurita et al [ 65 , 66 ] have demonstrated that an outer membrane vesicle-based vaccine was able to induce long-term T RM memory cells as well as protect mice against pertactin-deficient B. pertussis isolates. Replacing aluminum adjuvant in aP vaccine may enhance vaccine response and prolong protective immunity [ 67 ]. This includes the use of toll-like receptor (TLR) agonist (2, 4, 7, 9) and stimulator of interferon genes (STING) [ 68 ].…”
Section: Future Directionsmentioning
confidence: 99%
“…New vaccine strategies and formulations are needed to provide improved protection for vulnerable populations, such as infants and older adults (i.e., elderly). 1 Adjuvants are critical components of vaccine formulations that can significantly increase immunization efficacy, primarily by functioning as agonists of pattern-recognition receptors (PRRs) to stimulate innate immune cells. However, most adjuvanted vaccine formulations are not rationally selected or tailored to account for age-associated differences in innate immune responses, often resulting in suboptimal hyporesponsiveness and/or immunosenescent differences in translational vaccine outcomes.…”
Section: Introductionmentioning
confidence: 99%